Good anatomical outcome of orbital plasmacytoma following chemo-radiotherapy - Aimy Mastura ZY,; Othmaliza Othman,; Khairunisa AA,; Norshamsiah Md. Din, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Extramedullary plasmacytoma is a rare complication from multiple myeloma. We report a 56-year-old lady with underlying multiple myeloma who developed swelling over the left eye. It caused a non-axial proptosis, exposure keratopathy and visual acuity of counting fingers. A tissue biopsy revealed infiltration of tissue fragments with neoplastic plasma cells positive for CD138 and Kappa light chain restrictions consistent with plasmacytoma. Following radio-chemotherapy, the mass shrunk tremendously but her visual outcome remained poor.